(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Urethral prolapse is a rare cause of vaginal bleeding in prepubertal females and occurs more commonly in black girls. It is characterized by protrusion of the distal urethral mucosa at or beyond the level of the urethral meatus. It is often mistaken for sexual abuse in children because it presents with vaginal bleeding, creating anxiety among parents and confusion among clinicians. Case presentation: A 4-year-old girl presented to the outpatient department with a 2-day history of vaginal bleeding. However, no lower abdominal pain was reported. Sexual abuse was initially suspected. A diagnosis of urethral prolapse was made during examination under anesthesia. Surgical excision and postoperative care were performed. Conclusion: Urethral prolapse, although rare, can occur in prepubertal black girls and is managed either surgically or through conservative approaches.